The Role of Social Cohesion of the Beledan Koke Bale in Strengthening the Character of the Lewokluok Indigenous Community in East Flores - Rikardus Pande; Mariana Marta Towe; Elisabeth Ene Lein; Vinsensius Crispinus Lemba (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2026)
strengthening the character of the Lewokluok indigenous community in East Flores. Sociosemiotic theory as a scalpel for the meaning and social function of carved motifs on beledan koke bale. The research uses a qualitative descriptive method to examine the symbolic meaning of beledan in the lives of the Lewokluok indigenous community. Data was collected through in-depth interviews, participatory observation, and FGD with traditional leaders. The data was analyzed using the Miles and Huberman interactive model, which includes the stages of data reduction, data presentation, and drawing conclusions. The study results show that there are 18 beledan on the koke bale, representing the identities of 16 indigenous tribes. Each beledan has carved motifs that contain symbolic meanings related to leadership and courage, struggle, fertility and love, religiosity, family ties, love, service, solidarity, as well as health and survival. Meanwhile, the social cohesion that is conveyed through the beledan koke bale plays a role in strengthening the character of the Lewokluok indigenous community in three main ways: (1) to be a symbol of collective identity that fosters a sense of togetherness, love for others, and respect for ancestral heritage; (2) strengthening social solidarity so as to form a character of mutual trust between ethnic groups, a tolerant attitude towards diversity; and (3) deepening spirituality that fosters a humble character, gratitude, inner peace, and empathy in community life.